Quasi-static and dynamic compressive properties and deformation mechanisms of 3D printed polymeric cellular structures with Kelvin cells. (October 2019) - Duan, Yu; Du, Bing; Shi, Xiaopeng; Hou, Bing; Li, Yulong
Highlights: The effects of relative density and loading rate on the compressive responses of 3D printed Kelvin foams are studied. We establish the Gibson–Ashby equations of 3D printed Kelvin foams. The deformation mechanisms of Kelvin foams are dominated by the relative density. The loading rate significantly influences the position of the intensive deformation zone. A classification map of deformation modes is proposed illustrating the critical relative density and impact velocity. Abstract: The effects of the relative density and loading rate on the compressive response, deformation pattern and energy absorption of 3D printed polymeric Kelvin foams are investigated experimentally and computationally. A high-speed camera is used to record the loading processes of different cubic specimens, and the deformation distribution is calculated using the digital imaging correlation (DIC) method. Experimental results show that the elastic modulus and plateau stress increase with increasing relative density, which obeys the Gibson-Ashby polynomial scaling law. Four different deformation modes are observed in experiments for the specimens with different relative densities and at different loading rates. Further numerical results indicate the presence of a critical relative density, below which the Kelvin foams deform primarily by cell edges bending, and beyond which the cell membranes stretching dominates. It is also found that the position of the deformation bands is dominated by the loading rate. These findings can be used to explain the existing of four deformation modes observed in experiments. In conclusion, a mode classification map is proposed to clarify the effects of the relative density and loading rate on the deformation modes of Kelvin foams based on the experimental and numerical results.